2002
DOI: 10.1007/0-306-46838-7_40
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Oxidative Damage to Dna by Tairome and Taurine Analogs

Abstract: Abstract:Taurine has been suggested to have cytoprotective actions via a number of different mechanisms. The role of taurine in protecting DNA from oxidative damage has received only limited attention. The aim of the present studies was to test the hypothesis that taurine might act to attenuate oxidative damage to DNA caused by free radicals generated by iron-stimulated catecholamine oxidation in the presence of H2O2. Calf thymus DNA (100 µg/tube) was exposed to a reaction mixture containing: ferric chloride (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 25 publications
4
39
0
Order By: Relevance
“…31,32 HTau also has been shown to protect against cell injury. 33, 34 We therefore assessed its capacity to protect against liver injury in the setting of oxidative stress. Despite a decreased PUFA/MUFA ratio, HTau did not prevent t-BHP liver injury, as obvious from increased serum ALT.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 HTau also has been shown to protect against cell injury. 33, 34 We therefore assessed its capacity to protect against liver injury in the setting of oxidative stress. Despite a decreased PUFA/MUFA ratio, HTau did not prevent t-BHP liver injury, as obvious from increased serum ALT.…”
Section: Discussionmentioning
confidence: 99%
“…2F), consistent with the likelihood that TRAP1 KO cells are constitutively exposed to elevated oxidative stress. Interestingly, taurine, hypotaurine, and propionylcarnitine have all been reported to protect cells from oxidative stress (23)(24)(25)(26)(27)(28)(29). Thus, the elevated levels of these metabolites in TRAP1 KO cells (Fig.…”
Section: Trap1 Deficiency Is Associated With Increased Mitochondrial mentioning
confidence: 96%
“…Many studies revealed that, taurine (derivative of the amino acid cysteine, obtained from the bile of animals) can inhibit the cellular disorders by decreasing the oxidative stress and had a protective role against substances that induce liver fibrosis (Wingenfeld et al, 1996;You and Chang, 1998;Hardikar et al, 2001;Waer and Edress, 2006). Furthermore, Messina and Dawson (2000) mentioned that, MSG could be decreased the taurine level and consequently induce the accumulation of collagen fibers in the liver cells (Chen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%